Tuberculosis associated chronic obstructive pulmonary disease. (23rd March 2017) - Sarkar, Malay; Srinivasa,; Madabhavi, Irappa; Kumar, Kushal
Abstract: Objectives: Reviewed the epidemiology, clinical characteristics, mechanisms, and treatment of tuberculosis associated chronic obstructive pulmonary disease. Data source: We searched PubMed, EMBASE, and the CINAHL from inception to June 2016. We used the following search terms: Tuberculosis, COPD, Tuberculosis associated COPD, and so forth. All types of study were chosen. Results and Conclusion: Chronic obstructive pulmonary disease (COPD) and tuberculosis are significant public health problems, particularly in developing countries. Although, smoking is the conventional risk factor for COPD, nonsmoking related risk factors such as biomass fuel exposure, childhood lower‐respiratory tract infections, chronic asthma, outdoor air pollution, and prior history of pulmonary tuberculosis have become important risk factors of COPD, particularly in developing countries. Past history of tuberculosis as a risk factor of chronic airflow obstruction has been reported in several studies. It may develop during the course of tuberculosis or after completion of tuberculosis treatment. Developing countries with large burden of tuberculosis can contribute significantly to the burden of chronic airflow obstruction. Prompt diagnosis and treatment of tuberculosis should be emphasized to lessen the future burden of chronic airflow obstruction.